Koleksi Audio-Visual Sebagai Alat Promosi Budaya: Studi Kasus Perpustakaan Korean Culture Center - Abdi Mubarak Syam (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2016)
This article discusses the collection of audio-visual as a tool of cultural promotion in Korean Culture Center (KCC) library. This tyoe of research is qualitative research using the case study method. The case study method is used to determine how the audio-visual collection becomes a tool of cultural promotion in KCC library. Audio-visual collections in library increased function not only as a conduit of information for teaching or research, but also a tool of cultural promotion. It happened in the library embassies in each country, such as in the KCC library in Jakarta. KCC library makes audio-visual collections as s tool of cultural promotion of their country through the collection of Korean drama or Korean music.